Exploring the Morphosyntactic Features of Spoken English Used by Selected Sri Lankan Parliamentarians from 2019- 2024 - Maheshwaralingam, G.; Senaweera, S.A.T.P.; Gamage, G.D.U.P.K. (University of Jaffna, 2025)
English language is one of the widely used languages in the world and its influence is felt across so many fields in the world, (such as Commerce, Politics, Global Affairs, Security, Health, Education, Technology and so forth), that it has become imperative for those in highly responsible positions to master English. In Sri Lanka, the Parliament is the ultimate sovereign body where members who represent the entire population are elected for serving the best interests of the people. Therefore, as indicated above, it is incumbent upon the members of Parliament to be well-versed in their field as well as the English language in order to maintain international relations with state and non- state actors, find new opportunities for the country and develop the country as a whole. However, several Parliamentarians in the country are not in a position to express themselves in English, except a few. Those who can handle English exhibit diverse morphosyntactic features in their spoken English. Hence, it is important to understand the morphosyntactic features of the spoken English used by Sri Lankan Parliamentarians. The present study explores the unique morphological and syntactic features found in the spoken English of selected Parliamentarians from 2019-2024.The present study employs a qualitative research approach. Parliamentary speeches, and interviews of the selected Parliamentarians served as the primary source of data for this research. Purposive sampling technique was employed by the researcher to gather adequate data from the parliamentarians representing Sinhalese, Tamils and Muslims in the country. The data from the research were thematically analyzed to align with the research questions. The overall findings of the study revealed the following morphological features such as formal and informal diction, reduction and contraction, ellipsis and morphological simplification, disregard for inflectional and derivational features, number, and case, reduplication, morphological repairs and the use of high-flown language. Furthermore, the syntactic features included declarative and interrogative structures, different types of answers, ellipsis, self-corrections, overlapping talk ,turn-taking, completion and in completion of turns, changes in word order, using phrases as sentences, collocation errors, misuse of tenses, lack of awareness on prepositional phrases and time expressions, disregard for discourse markers and conjunctions and formal and informal expressions. The analysis of the data revealed that those members of Parliament who are well- versed in English or who have received their education in English medium could speak English in a comprehensive way, while those who are not so competent in English did not figure themselves well in English and hence, made many errors in their spoken English, sometimes even hindering the mutual intelligibility, thus affecting the efficiency of their role. The research concludes that the selected Sri Lankan Parliamentarians (2019-2024) exhibited unique Morphosyntactic features in their spoken English, influenced by their competency in English. Thus, it is very important for the Parliamentarians to master the English language to efficiently deal with diverse linguistic people in the country and different stakeholders and political and non-political actors across the globe.
Keywords: Members of Parliament; International relations; Morphosyntactic features